Combining GAs and RBF Neural Networks for Fuzzy Rule Extraction from Numerical Data - Wallace, Manolis; Tsapatsoulis, Nicolas (My University, 2005)
The idea of using RBF neural networks for fuzzy rule extraction from numerical data is not new. The structure of this kind of architectures, which supports clustering of data samples, is favorable for considering clusters as if-then rules. However, in order for real if-then rules to be derived, proper antecedent parts for each cluster need to be constructed by selecting the appropriate subspace of input space that best matches each cluster’s properties. In this paper we address the problem of antecedent part construction by (a) initializing the hidden layer of an RBF-Resource Allocating Network using an unsupervised clustering technique whose metric is based on input dimensions that best relate the data samples in a cluster, and (b) by pruning input connections to hidden nodes in a per node basis, using an innovative Genetic Algorithm optimization scheme.
Keywords: Neural networks (Computer science)--Congresses; Artificial intelligence--Congresses